2019
DOI: 10.3390/rs11111394
|View full text |Cite
|
Sign up to set email alerts
|

Twenty Years of ASTER Contributions to Lithologic Mapping and Mineral Exploration

Abstract: The Advanced Spaceborne Thermal Emission and Reflection Radiometer is one of five instruments operating on the National Aeronautics and Space Administration (NASA) Terra platform. Launched in 1999, the Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) has been acquiring optical data for 20 years. ASTER is a joint project between Japan’s Ministry of Economy, Trade and Industry; and U.S. National Aeronautics and Space Administration. Numerous reports of geologic mapping and mineral explorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 143 publications
0
33
0
2
Order By: Relevance
“…Due to sensor failure, SWIR data acquired since April of 2008 is not available [82]. Nonetheless, as mentioned before, ASTER's specific characteristics greatly contributed to mineral exploration, especially in alteration mapping associated with gold and porphyry copper deposits [53,54]. A review of the different "on-demand" ASTER products can be found in the work of Pour and Hashim [83].…”
Section: Data Products Used For the Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to sensor failure, SWIR data acquired since April of 2008 is not available [82]. Nonetheless, as mentioned before, ASTER's specific characteristics greatly contributed to mineral exploration, especially in alteration mapping associated with gold and porphyry copper deposits [53,54]. A review of the different "on-demand" ASTER products can be found in the work of Pour and Hashim [83].…”
Section: Data Products Used For the Researchmentioning
confidence: 99%
“…The swath width is 13.1 km. Despite lacking a TIR sensor, WorldView-3 has good potential for mineral mapping since its bandpasses are very similar to the ASTER VNIR-SWIR ones [4,54]. Additionally, such high resolution can help to tackle the vegetation problems due to the sensors' ability to map between trees [4].…”
Section: Data Products Used For the Researchmentioning
confidence: 99%
“…In the ASTER science team, several calibration approaches (i.e., preflight, onboard, vicarious, cross, lunar, and inter-band calibrations) have been performed and discussed for the ASTER VNIR radiometers. Vicarious and lunar calibration approaches have been selected [32], and the radiometric degradation curves for ASTER VNIR processing have been derived from the vicarious and lunar calibrations. The basic ideas (i.e., reason and philosophy) of this selection are explained as follows.…”
Section: Selection Of the Calibration Approachmentioning
confidence: 99%
“…The Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) sensor was launched in 18 December, 1999, onboard the first NASA's Earth Observation System (EOS) series of satellites, Terra [10,11]. The ASTER covered a wide spectral region with 14 bands from visible to thermal infrared with high spatial, spectral and radiometric resolution as shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%